Effect of zinc concentration and source on performance and carcass characteristics of feedlot steers - Caldera, Emmanuel, author; Engle, Terry, advisor; Wagner, John J., advisor; Pritchett, James G., committee member (Colorado State University. Libraries, 2012)
Three-hundred and sixty cross-bred steers (348.1 kg ± 28.9) were utilized to investigate the effects of zinc (Zn) concentration on performance and carcass characteristics of feedlot steers. Steers were blocked by weight and randomly assigned to one of the 5 supplemental Zn treatments (8 pens per treatment; 9 hd per pen). Treatments consisted of: 1) Control-50 (CON-50; 50 mg of supplemental Zn/kg DM from ZnSO4); 2) Methionine control [MetCON-50; 50 mg of supplemental Zn/kg DM from ZnSO4 plus MHA to equalize HMTBa concentrations across treatments; 3) Organic-50 (ORG-50; Control diet supplemented with 50 mg of Zn/kg DM from Mintrex Zn plus MHA to equalize HMTBa intake across treatments); 4) Organic-100 (ORG-100; Control diet supplemented with 100 mg of Zn/kg DM from MINTREX Zn plus MHA to equalize HMTBa intake across treatments 2-5); and 5) Organic-150 (ORG-150; Control diet supplemented with 150 mg of Zn/kg DM from Mintrex Zn). All steers were fed a typical high concentrate steam-flaked corn based finishing diet twice daily. Steers were individually weighed on d −1, 0, 144, and 145 and pen weighed on d 28, 56, 84, and 111. Ractopamine HCl was fed for the final 29 d of the finishing period to all treatments. On d 145, steers were transported to a commercial abattoir for slaughter. Initial and final body weight, ADG, DMI, and feed efficiency (g/f), were similar across treatments. However, there was a diff (P < 0.04) for ADG to be increased when MetCON-50 was compared to Con-50 on d-56 pen weigh and d-84 pen weigh (3.91, 4.42 ± 0.17 and 4.96, 4.29 ± 0.21 respectively). ADG was also increased (P <0.03) when the CON-50 treatment was compared to the ORG-50 treatment for the d-84 pen weigh period (4.96, 4.29 ± 0.21). There was a trend (P< 0.07) for gain:feed to be increased for the CON-50 when compared to MetCON-50 and ORG-50 for the d57-84 period (0.228, 0.198, 0.199 ± 0.01). Fat thickness, internal fat, hot carcass weight, KPH, marbling score, and dressing percentage were similar across treatments. Steers receiving ORG-150 had a greater (P < 0.03) yield grade compared to steers receiving ORG-50 (2.99 vs. 2.76 ± 0.08; respectively). Steers receiving 1080 Zn also had a greater (P < 0.01) yield grade compared to steers receiving ORG-100 (2.99 vs. 2.68 ± 0.08; respectively). There was a trend (P < 0.07) for steers receiving MetCON to have a greater yield grade compared to CON-50 (2.82 vs. 2.67 ± 0.08; respectively). In addition, liver biopsies and blood samples were analyzed for Zn, Cu, and Fe concentrations as well as alkaline phosphatase in the blood. Initial liver biopsies were similar in Cu and Fe among treatments. Whereas, the Zn concentrations were greater (P < 0.01) in the CON-50 group compared to the Methionine treatment group (218.7 vs. 170.2 ± 12.9). Day 111 liver Zn concentrations tended ( P < 0.05) to be lower for CON-50 and MetCON-50 treatments compared to ORG-50 treatment, while no other differences were noted among treatments (117.8, 123.7 vs. 158.0 ± 16.1). Day-0 plasma results indicate levels of Zn, Cu, and Fe to be similar among treatments with a trend (P < 0.07) in Fe concentrations to be less in the MetCON-50 when compared to the CON-50 treatment (4.71 vs. 1.70 ± 0.85). As for the d-111 plasma analysis indicated no differences among treatments in regards to Zn, Cu, and Fe concentrations. The d-144 plasma analysis indicated no differences (P > .05) in Zn, Cu, and Fe concentrations among treatments. The alkaline phosphatase values for d-0, d-111, and d-144 were similar across treatments, yet the alkaline phosphatase means for each treatment increased over time. These data indicate that under conditions of this trial, increasing Zn concentration in the diet above NRC recommendations has little impact on performance, however, may impact lipid partitioning in steers.
Keywords: carcass characteristics; zinc; performance; feedlot